Fenomena Konten Prank Terhadap Anak dalam Media Sosial dan Dampaknya Terhadap Moralitas Anak - Zahra, Oliviea Novrimada; Az-Zahra, Salsabila; Fatimah, Zanadia Manik; Syahri, Moch; Zulfikar, Moh Fikri (Universitas Bina Sarana Informatika, 2024)
This research aims to describe the phenomenon of prank content on social media TikTok and YouTube and its impact on children's morality. Prank content is defined as content that contains the creator's actions or tricks to prank other people with the aim of joking and entertaining. Morality is defined as rules of value about what should be done in interacting with other people. This study used a descriptive qualitative method. This research data is in the form of prank content against children. The research data source is prank video content on the Tik Tok and YouTube applications. The results obtained from this research were that 8 forms of prank were found, namely, (1) breaking eggs, (2) kidnapping children, (3) leaving children in the mall, (4) smearing feces, (5) invisible prank, (6) black eyes, (7) hitting cats, and (8) pulling chairs. The content of the prank has an impact on moral values, namely, (1) respecting fellow human beings, (2) respecting women, (3) respecting other people's opinions and being willing to live side by side with other people who are different, (4) tolerance. feeling, fair, likes to serve, friendly, loyal, polite and keeps promises, (5) democratic attitude: non-discriminatory and non-repressive, (6) respect for sexuality and family life, (7) attitude towards the nation and state, love of the homeland, and (8) traditional values and rules of courtesy.